CACHEXIA WITH LOW BLOOD PRESSURE IN YOUNG WOMEN - E. N. Kudryavoeva; V. M. Baev; O. A. Igumnova; T. YU. Agafonova; E. A. Vagner (Евразийский Кардиологический Журнал)
The aim of the study was to study the prevalence of cachexia among young women with idiopathic arterial hypotension (IAH).